FORENSIC MEDICAL CRITERIA FOR ASSESSING CEREBROSPINAL FLUID CIRCULATION DISORDERS IN FATAL TRAUMATIC BRAIN INJURIES - Ismailova Mehriban Olimbaevna (Bright Mind Publishing, 2025)
In almost all cases of traumatic brain injury (TBI), there is displacement and deformation of the brain, followed by its return to its original position. This is inevitably accompanied by dynamic redistribution of cerebrospinal fluid (CSF) in the subarachnoid space and ventricular system of the brain. This highlights the relevance of studying the thanatogenesis of brain injuries in TBI, particularly the CSF circulation system. A retrospective analysis of traumatic brain injuries was conducted in this study. For the first time, morphological and morphometric indicators of CSF circulation were examined, and the main stages of thanatogenesis in fatal TBIs were determined. A systematic analysis of CSF circulation disorders in traumatic brain injury was performed, and expert criteria for assessing its severity and timing were developed.
Keywords: TBI, brain, cerebrospinal fluid circulation, thanatogenesis, morphology, morphometry, expert criteria.